Channel-forming activity and channel size of the RTX toxins ApxI, ApxII, and ApxIII of Actinobacillus pleuropneumoniae. - Maier, E (1996)
The determinants of the Actinobacillus pleuropneumoniae RTX toxins ApxI, ApxII, and ApxIII were expressed in an Escherichia coli strain. The toxins were concentrated from the supernatants of cell cultures. The addition of the toxins to the aqueous-phase-bathing lipid bilayer membranes resulted in an increase in the membrane conductance when membranes made of asolectin or phosphatidylethanolamine were used. The toxins were relatively inactive in membranes made of other lipids. The membrane activity (i.e., the number of channels formed at a given Apx concentration) was different for each of the three Apx toxins. That of ApxI, which has the strongest cytotoxic activity, was highest, followed by that of ApxIII and ApxII, which is the least cytotoxic. The conductance increases of ApxIII and ApxII were smaller by factors of 10 and 50, respectively, than that of ApxI under otherwise identical conditions. Single-channel experiments demonstrated that all three Apx toxins formed ion-permeable channels of different conductances. The major open state was approximately the same for the two hemolytic toxins ApxI and ApxII (540 and 620 pS in 0.15 M KCI), whereas the single-channel conductance of the nonhemolytic ApxIII was approximately one-fifth of that of the other two toxins (95 pS). Experiments with different salts suggested that the Apx channels of A. pleuropneumoniae were exclusively cation selective because of negative charges localized at the channel mouth. Analysis of the single-channel data using the Renkin correction factor suggested that the Apx toxins formed aqueous channels with different diameters for the three toxins. Pore-forming properties of the Apx toxins were compared with those of other RTX toxins. All of these toxins have common features and form channels that are transient but have different sizes as judged from the different single-channel conductances.